Glutathione production using magnetic fields generated by magnets - Santos,Lucielen Oliveira dos (2012)
The objective of this work was to study the production of GSH by Saccharomyces cerevisiae ATCC 7754 in a fermentor (5 L) using a cell recycle system with magnets. The fermentation conditions were 20°C, 500 rpm, 5% (v/v) of inoculum, pHinitial 5, 1.1 vvm aeration and total fermentation time of 72 h. The time of application of MF ranged from 24, 48 or 72 h. In comparison to the control experiment, the best results were obtained with 72 h of application of MF. The cell concentration reached 19.5 g/L and GSH concentration was 271.9 mg/L that corresponded to an increase of 2.63 and 32.1% compared to the control experiment, respectively.